Biliary Dyskinesia as a Rare Presentation of Metastatic Breast Carcinoma of the Gallbladder: A Case Report - A. Markelov; H. Taheri; K. Vunnamadala; G. Ibrahim (Case Reports in Pathology)
Background. Breast carcinoma is the most common malignancy in women worldwide. It is most commonly associated with metastases to the liver, lung, bone, and the brain. Invasive lobular carcinoma is a less common pathology with slightly higher metastases to the upper gastrointestinal tract. Invasive lobular carcinoma metastasis to the gallbladder is extremely rare. Method. In this paper we are presenting a case of a 67-year-old female with metastases of invasive lobular breast cancer to the gallbladder six years after her therapy. Conclusion. This case clearly signifies the nature of the micrometastatic foci of the invasive lobular carcinoma even many years after a successful treatment.